An Adaptable Security Framework for Wireless Sensor Networks - El Zouka, Hesham A. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The design of secureÂ and survivableÂ nodes is one of the most vital issues in designing energy-efficient protocols for wireless sensor network where the energy, memory and computational power of sensor nodes are limited. In this paper, some of the challenges facing the wireless sensor networks are discussed in attempting to prolong the battery lifetime of the nodes, and to secure the communication channel. While most of these attacks can be dealt with through cryptographic security protocols provided by key management schemes, there are always a few that manage to really cause problems. One such attack that is most common and significant in WSNs is cloning attack. In clone attack, the intruder tries to capture and compromise some nodes and inject them into several locations throughout the network in order to conduct other types of attacks. Moreover, if this attack is not detected early, then these replicated injected nodes will consume a large amount of the network resources. Several possible approaches are suggested to improve the security, authentication protocols, and key management schemes in WSNs.Â Furthermore, utilizing the existing security protocols in wireless sensor networks has led us to propose a secure framework which incorporates security protocols in a way that minimizes the energy consumption of the sensor nodes. Our algorithm ensures data confidentiality, node authentication, and data integrity while remaining within acceptable memory, time and energy constrains.